Highlighting Compensation Policies in Hospitality Industries during the COVID-19 Pandemic - Ginting, Josafat Gracia; Sopiah (Brilliant International Journal Of Management And Tourism, 2022)
This article investigates how compensation to hospitality industries has been conducted during the COVID-19 pandemic. Using documentary study, the writers made use of Google scholar and the Garuda portal database to collect data. Some primary keywords were employed to search relevant published articles such as compensation in a hotel during the COVID-19 pandemic. This study finds that hotel owners modified policies by giving only 50% of their salary. Meanwhile, the government covers another 50% of financial support to help the employees. Applying for compensation with support, promotion, and money will motivate employees to work. For the consumers, hotels lowered the price of the rooms. In addition, hotels also paid very careful attention to sanity issues and hotel service quality. It turns out that these adapted compensation policies have resulted in positive impacts on employees and consumers.